Differences of Streptococcus mutans adhesion between artificial mouth systems: a dinamic and static methods - Aryan Morita; H. Dedy Kusuma Yulianto; Susmira Delta Kusdina; Nunuk Purwanti (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Various materials have been used for treating dental caries. Dental caries is a disease that attacks hard tissues of the teeth. The initial phase of caries is a formation of bacterial biofilm, called as dental plaque. Dental restorative materials are expected for preventing secondary caries formation initiated by dental plaque. Initial bacterial adhesion is assumed to be an important stage of dental plaque formation. Bacteria that recognize the receptor for binding to the pellicle on tooth surface are known as initial bacterial colonies. One of the bacteria that plays a role in the early stage of dental plaque formation is Streptococcus mutans (S. mutans). Artificial mouth system (AMS) used in bacterial biofilm research on the oral cavity provides the real condition of oral cavity and continous and intermittent supply of nutrients for bacteria. Purpose: This study aimed to compare the profile of S. mutans bacterial adhesion as the primary etiologic agent for dental caries between using static method and using artificial mouth system, a dinamic. method (AMS). Method: The study was conducted at Faculty of Dentistry and Integrated Research and testing laboratory (LPPT) in Universitas Gadjah Mada from April to August 2015. Composite resin was used as the subject of this research. Twelve composite resins with a diameter of 5 mm and a width of 2 mm were divided into two groups, namely group using static method and group using dynamic method. Static method was performed by submerging the samples into a 100µl suspension of 1.5 x 108 CFU/ml S. mutans and 200µl BHI broth. Meanwhile AMS method was carried out by placing the samples at the AMS tube drained with 20 drops/minute of bacterial suspension and sterile aquadest. After 72 hours, five samples from each group were calculated for their biofilm mass using 1% crystal violet and read by a spectrofotometer with a wavelength of 570 nm. Meanwhile, one sample from each group was taken for its surface image using Scanning Electron Microscope (SEM). Result: The results showed that S. mutans biofilm mass in the group using static method was 0.34, while in the group using AMS method was 0.09. The results of the statistical analysis then showed that there was a significant difference (p=0.02) in the formation of bacterial biofilm mass between those groups. SEM image in the group using static method also showed that the attachment of S. mutans was more numerous and had a longer chain than in the group using AMS method. Conclusion: There is a difference in the profile of S. mutans bacterial adhesion between using AMS method and static method.